Design and Implementation of Hybrid Renewable Energy System Using DFIG and Multilevel Inverter - Faizul Hilmy, Muhamad Hanis (Universiti Teknologi PETRONAS, 2020)
The hybrid renewables energy of wind and photovoltaic (PV) are becoming popular nowadays for power generation especially in the windy and sunny area. Doubly fed induction generator (DFIG) that is driven by the wind turbine used in this project consist of the rotary part for maximum wind energy captured and the stationary part focus on supplying the AC grid load. The DFIG rotor needs voltage and frequency excitation by using the wind energy conversion system (WECS) to balance the important parameters of the stator to get the best output quality. Maximum power point tracking (MPPT) is used to extract the power capability of the hybrid renewables of PV-wind. The neutral point clamped (NPC) or so called the diode clamped multilevel inverter used in this system is to convert the regulated DC signal into AC signal through filtering circuit before supplying it to the 3-phase AC grid load. The power converters unit such as the diode rectifier and boost regulator will be implemented in the system. The system design used the AC-DC-AC conversion system.